On certain meromorphic functions with positive coefficients - Young Chang Kim; Sang Hun Lee; Shigeyoshi Owa (International Journal of Mathematics and Mathematical Sciences)
In this paper, we introduce a new class TP(α) of meromorphic functions with positive coefficients in D={z:0<|z|<1}. The aim of the present paper is to prove some properties for the class Tp(α).